Tanggungjawab Debitur Atas Utang Piutang Dengan Menggunakan Persetujuan Isteri atau Suami Palsu Yang Dilakukan Di Koperasi - Erianto Krisbiantoro; Bambang Arwanto (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This research is based on the 1945 Constitution of the Republic of Indonesia, Law no. 17 of 2012 concerning cooperatives, the Criminal Code and the Civil Code or other regulations that are relevant or relevant to quote, as well as theories from library materials that are in accordance with the problems raised in this study. The conclusion of this study is that the first factor that causes the debtor to falsify the consent of a fake husband or wife can be due to several factors, namely: the existence of a disharmonious relationship with the husband or wife, the desire of the debtor to reap personal benefits, the desire of the debtor to obtaining benefits for other people, the existence of such forgery is for corporate crimes, or just to facilitate the process of realizing credit applications by debtors. Secondly, the accountability of debts and receivables in cooperatives with the approval of a fake wife or husband then is a criminal act of forgery which can be subject to Article 263 of the Criminal Code. fake letters or falsifying letters, Article 264 of the Criminal Code falsifying authentic deeds or Article 266 of the Criminal Code (ordering to enter false information into an authentic deed. Thirdly, the Accountability of the Debtor for Debts and Receivables in a civil manner Using Approval I fake wife or husband that is done in a cooperative. The liability of the debtor in the event of a default action carried out on the credit agreement contract carried out by the debtor of the cooperative, where in the event of a default, the debtor must remain accountable for the contract he has made on the basis of Articles 1243, 1266, 1267. The Civil Code (KUHPer). In essence, the debtor is required to pay compensation, the creditor asks for the cancellation of the agreement through the court, or the creditor can ask for the fulfilment of the agreement, the fulfilment of the agreement with compensation and the cancellation of the agreement with compensation.Keywords: Responsibility; Accounts Payable; Counterfeit AbstrakPenelitian ini didasarkan undang-undang dasar NKRI 1945, undang-undang no. 17 tahun 2012 tentang perkoperasian, Kitab Undang-undang Hukum Pidana dan Kitab undang-undang hukum perdata atau peraturan lainya yang berkaitan atau relefan untuk di kutip, serta teori-teori dari bahan pustaka yang sesuai dengan permasalahan yang diangkat dalam penelitian ini. Adapun kesimpulan dari penelitian ini adalah yang pertama factor penyebab debitur melakukan pemalsuan terhadap persetujuan suami atau istrei palsu bisa dikarenakan beberapa factor yakni : adanya hubungan yang tidak harmonis dengan pasangan suami atau isteri, adanya keinginan dari debitur untuk meraup keuntungan pribadi, adanya keinginan dari debitur untuk memperoleh keuntungan untuk oranglain, adanya pemalsuan tersebut untuk kejahatan koorporasi, atau hanya untuk memudahkan proses realisasi pengajuan kredit oleh debitur.yang kedua pertanggungjawaban utang piutang di koperasi atas persetujuan istri atau suami palsu maka hal tersebut merupakan tindak pidana pemalsuan yang bisa dikenai Pasal 263 KUHPidana membuat surat palsu atau memalsukan surat, Pasal 264 KUHPidana memalsukan akta-akta otentik atau Pasal 266 KUHPidana (menyuruh memasukkan keterangan palsu ke dalam suatu akta otentik.yang ketiga Pertanggungjawaban Debitur Atas Utang Piutang secara perdata Dengan Menggunakan Persetujuan Isteri Atau Suami Yang Palsu Yang Dilakukan Di Koperasi. Pertanggungjawaban debitur tersebut dalam hal tindakan wanprestasi yang dilakukan atas akad perjanjian kredit yang dilakukan oleh debitur dikoperasi, dimana dalam hal telah terjadi wanprestasi maka debitur harus tetap mempertanggungjawabkan akad yang telah dibuatnya dengan landasan pada Pasal 1243, 1266 , 1267. Kitab Undang-Undang Hukum Perdata (KUHPer). Yang intinya Debitur diharuskan membayar ganti rugi, Kreditur minta pembatalan perjanjian melalui pengadilan, atau Kreditur dapat minta pemenuhan perjanjian, pemenuhan perjanjian disertai ganti rugi dan pembatalan perjanjian dengan ganti rugi.Kata Kunci: Tanggungjawab; Utang Piutang; Pemalsuan